2022
DOI: 10.1021/acs.jcim.2c00601
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Binding Free Energy Method from End-State MD Simulations

Abstract: Herein, we introduce a new strategy to estimate binding free energies using end-state molecular dynamics simulation trajectories. The method is adopted from linear interaction energy (LIE) and ANI-2x neural network potentials (machine learning) for the atomic simulation environment (ASE). It predicts the single-point interaction energies between ligand–protein and ligand–solvent pairs at the accuracy of the wb97x/6-31G* level for the conformational space that is sampled by molecular dynamics (MD) simulations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Accurate prediction of protein-ligand binding affinity remains one of the grand challenges of computational chemistry and biology. [1][2][3] With the ever increasing amount of high-resolution experimentally determined protein-ligand structures, 4 the binding affinity prediction methods have switched from physicsbased [5][6][7][8][9][10][11] to empirical scoring functions [12][13][14][15] and knowledgebased, 16,17 and in the last decade to machine learning [18][19][20][21][22][23][24][25][26][27] and deep learning based methods. [28][29][30][31][32][33][34][35][36][37][38] Especially, deep learning is an end-to-end method that is ideally suited to find hidden nonlinear relationships 39 between 3D protein-ligand complex structures and binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate prediction of protein-ligand binding affinity remains one of the grand challenges of computational chemistry and biology. [1][2][3] With the ever increasing amount of high-resolution experimentally determined protein-ligand structures, 4 the binding affinity prediction methods have switched from physicsbased [5][6][7][8][9][10][11] to empirical scoring functions [12][13][14][15] and knowledgebased, 16,17 and in the last decade to machine learning [18][19][20][21][22][23][24][25][26][27] and deep learning based methods. [28][29][30][31][32][33][34][35][36][37][38] Especially, deep learning is an end-to-end method that is ideally suited to find hidden nonlinear relationships 39 between 3D protein-ligand complex structures and binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Our custom script (deepQM), an extension to our previous work, 38 to do free energy calculations from ANI applied as post-MD simulations, is written in Python 3.9 and uses ASE libraries to calculate ANI singlepoint energies of the given A-B complex structure (e.g., A = ligand, L; B = solvent, S). As an end-to-end process with the DFT [39][40][41] accuracy, solvation free energy is predicted from LS complex, free ligand and solvent (water) structures, all of which are extracted from the trajectories of classical MD simulations of aqueous ligand system.…”
Section: Resultsmentioning
confidence: 99%
“…15 Finally, a new strategy from Akkus et al to estimate binding free energies using end-state molecular dynamics simulation based on LIE and ANI-2x neural network potentials predicts the single-point interaction energies between ligand−protein and ligand− solvent pairs at the accuracy of the wb97x/6-31G* level. 16…”
Section: Free-energy Calculationsmentioning
confidence: 99%
“…In another study by Gusev et al, it was demonstrated that the combination of active learning with automated machine learning and free-energy calculations yields at least 20-fold speedup relative to naïve brute force approaches . Finally, a new strategy from Akkus et al to estimate binding free energies using end-state molecular dynamics simulation based on LIE and ANI-2x neural network potentials predicts the single-point interaction energies between ligand–protein and ligand–solvent pairs at the accuracy of the wb97x/6-31G* level …”
Section: Machine Learning and Free-energy Calculationsmentioning
confidence: 99%